2019
DOI: 10.1093/ageing/afz115
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s a tough decision’: a qualitative study of proxy decision-making for research involving adults who lack capacity to consent in UK

Abstract: Background Research into dementia and other conditions connected with cognitive impairments is essential but conducting research with populations who lack capacity to provide consent involves a number of ethical, legal and practical challenges. In England and Wales, family members can act as a consultee or legal representative on behalf of someone who lacks capacity. However, there is a paucity of research about how family members make decisions concerning research participation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 23 publications
(26 reference statements)
0
57
0
Order By: Relevance
“…While empirical methods have support as a good way of grounding ethics, it is also important for ethical analysis to be grounded in the facts and reality of a situation [13]. We conducted a qualitative study to explore the experiences of family members in England and Wales who have acted as a research proxy [14], using a multiple-analytic approach to examine the data through multiple lenses. Pluralistic qualitative analyses have been found to be valuable in providing a multi-layered understanding of phenomena which possess ontological and epistemological multiplicity and multidimensionality [15].…”
Section: Developing a More Empirically Grounded Accountmentioning
confidence: 99%
See 1 more Smart Citation
“…While empirical methods have support as a good way of grounding ethics, it is also important for ethical analysis to be grounded in the facts and reality of a situation [13]. We conducted a qualitative study to explore the experiences of family members in England and Wales who have acted as a research proxy [14], using a multiple-analytic approach to examine the data through multiple lenses. Pluralistic qualitative analyses have been found to be valuable in providing a multi-layered understanding of phenomena which possess ontological and epistemological multiplicity and multidimensionality [15].…”
Section: Developing a More Empirically Grounded Accountmentioning
confidence: 99%
“…Whilst data used for this study were collected primarily for a thematic analysis of the proxies' experiences of decision-making which has been previously reported [14,20], the aim of the interviews was also to capture ethical concepts, critically examine the previously developed framework [10], and further refine it based on updated concepts identified from the data. Interviews were conducted either face-to-face or by telephone.…”
Section: Data Collectionmentioning
confidence: 99%
“…We conducted a qualitative study with family members acting as proxies which showed that they use the patient's expressed wishes about research where these are available and, where these were not known, use their in-depth knowledge of the person's values and preferences to facilitate decisionmaking on their behalf [9]. However, other proxies described it as being a difficult and challenging decision.…”
Section: Review Of Existing Decision Aids For Proxiesmentioning
confidence: 99%
“…Improving the decision-making process was recognised as being much more than just ensuring the proxy had received adequate information. Proxies thought that greater decision support when considering research decisions would help in the future, which included orientating them towards considering the person's own views and preferences [9]. Proxies suggested that this support could take the form of a different sort of information sheet which covered their role as proxy decisionmaker, and that the DA should include items that they considered would support proxies when making decisions about research ( Table 2.…”
Section: Review Of Existing Decision Aids For Proxiesmentioning
confidence: 99%
See 1 more Smart Citation